Association of remittances with skilled delivery in Uganda, 2019/2020. - Chelsea Ducille; Richard Bilsborrow; Kavita Singh; Jon Hussey; Larissa Jennings Mayo-Wilson (PLOS Global Public Health)
There are significant disparities in maternal and child mortality ratios between high-income and low- and middle-income countries (LMICs). Despite large decreases in maternal and child mortality in recent decades, with programs such as the Safe Motherhood Initiative, the Sustainable Development Goals and the Millennium Development Goals in LMICs, these differences remain large. The objective of this study is to examine the association between the receipt of remittances received by households and skilled delivery among women reporting a recent birth. This study uses data from the household, woman, and community modules of the Uganda National Panel Survey (UNPS) from 2019/2020 to examine skilled delivery and skilled delivery with the use of safe birthing kits. Women of reproductive age with a birth within the last three years of data collection were included in the analysis. A cross-sectional analysis of 2019/2020 UNPS data is analyzed using logistic regression and a dose-response analysis plotting the estimated probabilities of skilled delivery and skilled delivery with use of safe birthing kits against increasing amounts of remittances. While no statistically significant associations were found between remittances and skilled delivery in the logistic model, the dose-response model did find such a relationship. Recommendations for future research in this topic area include improving questionnaire design to collect better data on remittances, utilizing longitudinal data with larger sample sizes, and examining mechanisms of money transfer.